Effects of Combined Abiotic Stresses Related to Climate Change on Root Growth in Crops - Sánchez-Bermúdez, Maria; del Pozo, Juan C.; Pernas, Mónica (Frontiers in Plant Science, 2022)
Climate change is a major threat to crop productivity that negatively affects food security worldwide. Increase in global temperatures are usually accompanied by drought, flooding and changes in soil nutrients composition that dramatically reduced crop yields. Against the backdrop of climate change, human population increase and subsequent rise in food demand, finding new solutions for crop adaptation to environmental stresses is essential. The effects of single abiotic stress on crops have been widely studied, but in the field abiotic stresses tend to occur in combination rather than individually. Physiological, metabolic and molecular responses of crops to combined abiotic stresses seem to be significantly different to individual stresses. Although in recent years an increasing number of studies have addressed the effects of abiotic stress combinations, the information related to the root system response is still scarce. Roots are the underground organs that directly contact with the soil and sense many of these abiotic stresses. Understanding the effects of abiotic stress combinations in the root system would help to find new breeding tools to develop more resilient crops. This review will summarize the current knowledge regarding the effects of combined abiotic stress in the root system in crops. First, we will provide a general overview of root responses to particular abiotic stresses. Then, we will describe how these root responses are integrated when crops are challenged to the combination of different abiotic stress. We will focus on the main changes on root system architecture (RSA) and physiology influencing crop productivity and yield and convey the latest information on the key molecular, hormonal and genetic regulatory pathways underlying root responses to these combinatorial stresses. Finally, we will discuss possible directions for future research and the main challenges needed to be tackled to translate this knowledge into useful tools to enhance crop tolerance.